A literatura feminina em Rondônia: uma breve historiografia - Jaquelene Costa de Souza (Das Amazônias)
This article reveals the importance of literature written by women in the North region. Its objective is to reveal, recognize and rescue poets and their works from the North region, mainly from the State of Rondônia, highlighting an unknown author, Julia Almeida Souza, from the Municipality of Guajará Mirim, RO. This demonstrates the presence and female resistance of Rondônia’s poets. Julia Almeida Souza's poems cover a variety of themes and styles, standing out for their simplicity, with a simple and direct style, using figures of speech to give multiple interpretations to the poems. The article follows a bibliographic research methodology and is qualitative in nature. Therefore, this study contributes to the appreciation of female expression literature produced in the State. As a theoretical tool, the authors Zolin (2009), Moura (1992), Pinto (2021), Mendes and Bueno (1984), Brada (1984), Cavalcante (2013), Lima (2011), among other sources, will be used. The bibliographical research carried out highlights not only the richness of literary production by female authors in the North region, especially in Rondônia, but also the need to recognize and rescue figures such as Julia Almeida Souza, whose work contributes significantly to the diversity and depth of local literary culture.